Clinical trial design for systemic agents in patients with brain metastases from solid tumours: a guideline by the Response Assessment in Neuro-Oncology Brain Metastases working group. Issue 1 (January 2018) - Camidge, D Ross; Lee, Eudocia Q; Lin, Nancy U; Margolin, Kim; Ahluwalia, Manmeet S; Bendszus, Martin; Chang, Susan M; Dancey, Janet; de Vries, Elisabeth G E; Harris, Gordon J; Hodi, F Stephen; Lassman, Andrew B; et al.
Summary: Patients with active CNS disease are often excluded from clinical trials, and data regarding the CNS efficacy of systemic agents are usually obtained late in the drug development process or not at all. In this guideline from the Response Assessment in Neuro-Oncology Brain Metastases (RANO-BM) working group, we provide detailed recommendations on when patients with brain metastases from solid tumours should be included or excluded in clinical trials of systemic agents. We also discuss the limitations of retrospective studies in determining the CNS efficacy of systemic drugs. Inclusion of patients with brain metastases early on in the clinical development of a drug or a regimen is needed to generate appropriate CNS efficacy or non-efficacy signals. We consider how to optimally incorporate or exclude such patients in systemic therapy trials depending on the likelihood of CNS activity of the agent by considering three scenarios: drugs that are considered very unlikely to have CNS antitumour activity or efficacy; drugs that are considered very likely to have CNS activity or efficacy; and drugs with minimal baseline information on CNS activity or efficacy. We also address trial design issues unique to patients with brain metastases, including the selection of appropriate CNS endpoints in systemic therapy trials.